Aerodynamic Investigations of Tailless Mini UAV by Using Subsonic Wind Tunnel - เจียจันทร์ วันชัย (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2018)
This paper presents a wind tunnel investigation of aerodynamic characteristics of Tailless Mini-UAV. The tests were performed at low subsonic speeds (Reynolds number - ). The experimental result was then compared and confirmed with numerical results obtain from Computational Fluid Dynamics (CFD). The experimental result shown that the Tailless Mini-UAV provides high aerodynamic efficiency by up to 22, which is desirable to enhance the aerodynamic performance in terms of both range and endurance. In additions, the Tailless Mini-UAV was also statically stable in longitudinal axis. In comparison with the numerical solutions, good agreement was observed for both lift and drag coefficient.